Perceptions of the People of Haruku Country Regarding Covid-19 Vaccination - Yulike Maryani Kaihatu; Fricean Tutuarima; Fatimah Sialana (CV. Rayyan Dwi Bharata, 2023)
This research is a qualitative descriptive study that aims to find out how the people of Haruku state perceive the covid-19 vaccination, and what the role of the government is in dealing with the covid-19 pandemic. This research was carried out in Haruku country. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved. Data collection techniques used are observation, interviews and documentation. The results of this interview can show that the people of Haruku Country have different views regarding the covid 19 vaccination. There are still many people in Haruku Country who view the covid 19 vaccination as a policy that does not bring benefits to the community, which actually has a lot of bad impacts on society. In addition, the people of Haruku Country consider that the implementation of the Covid-19 vaccination is a policy that violates people's rights, namely the right to refuse or receive vaccines. So that the role of the government and medical staff in Haruku Country is very important to convince the public about the importance of the Covid-19 vaccination through socialization that is being carried out. However, the socialization that was carried out also did not change one hundred percent of the public's perspective on Covid-19 vaccination.